TO EVALUATE THE CONDITION AND OUTCOME OF TUBERCULOSIS (TB) PATIENTS WITH DIABETES - Atif Ahmed; Kuldeep Kumar Poorani; Kashif Ali; Ramesh Kumar Suthar; Bedar Bakhat Khan; Kamran Ali Qureshi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Pakistan’s illness burden has shifted, with communicable diseases declining and noncommunicable diseases increasing significantly. This shift has created a debate about policy objectives and resource allocation between advocates for CDs like tuberculosis (TB) and those for NCDs like cardiovascular disease and diabetic mellitus (DM). The two-way link between tuberculosis (TB) and diabetes demonstrates that diabetes is an independent risk factor for getting TB, although TB can also cause impaired glucose tolerance (IGT) and may lead to diabetes. Objective: To evaluate the condition and outcomes of TB patients with diabetes. Place and Duration: This study was conducted in Bilawal Medical College Hospital Kotri from June 2023 to May 2024 Methodology: This study was conducted on newly registered pulmonary tuberculosis (PTB) patients with diabetes (DM) at our hospital. During the trial period, 1500 patients were registered and all were screened for DM using random blood sugar tests. A lab technician collected samples and analyzed them on-site, identifying 150 people with diabetes. Results: The study comprised 100 TB patients with diabetes. The most cases (34%) were found in 51 to 60 age range, with a male-to-female ratio of 3:1 Over ¼ of the participants were literate (25%) and ¾ of participants were illiterate(75%), the majority lived in urban slums (53%), and more than half came from the middle socioeconomic level (67%). Conclusion: TB patients with diabetes experienced significant increases in health status and cure rates at the end of treatment.